Synthesis of protoporphyrin coated superparamagnetic iron oxide nanoparticles via dopamine anchor - Kemikli, Nurufe; Kavas, Huseyin; Kazan, Sinan; Baykal, Abdulhadi; Ozturk, Ramazan (Elsevier Science Sa, 2010)
Dopamine conjugated protoporphyrin, PPD, was prepared by the coupling reaction of protoporphyrin IX and dopamine in the presence of dicyclohexylcarbodiimide (DCC) and N-hydroxysuccinimide (NHS) in DMF. The crude product was washed with ethanol-cyclohexane (1:1) mixture to remove dicyclohexylurea (DCU). Previously prepared Fe3O4 nanoparticles were coated with PPD (sub-7 nm monosize) by sonication in the methanol. The porphyrin coated Fe3O4 nanoparticles, PPDNP were separated by permanent magnet. The microstructure and magnetic properties of magnetic nanoparticles were characterized by XRD, TEM, FT-IR, and VSM. It is found that the nanoparticles have high crystallinity with distinct lattices and the magnetic measurements reveal their well-defined superparamagnetic behavior at room temperature. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Protoporphyrin IX; Dopamine; Fe3O4 nanoparticle; Magnetism